X‐ray structure analysis reveals β‐turn mimicry by N‐amino‐imidazolidin‐2‐ones†. Issue 5 (September 2015) - Doan, Ngoc‐Duc; Lubell, William D.
ABSTRACT: The conformation of the N‐amino‐imidazolidin‐2‐one (Aid) peptidomimetic was investigated using NMR spectroscopy and X‐ray crystallography. In solution, the tetrapeptide model p‐bromobenzoyl‐Aid‐l ‐Phe‐N′‐iso‐propylamide (1 ) exhibited shielded and solvent exposed amide protons indicative of a turn conformation. In the crystal lattice of1, four turn conformers were present in the unit cell differing primarily by the ring puckering of the Aid residue. Two pairs of β‐turn conformers were observed each possessing an intramolecular ten‐member hydrogen bond between the benzamide carbonyl and iso‐propylamine NH moieties. The pairs had types II and II′ β‐turn geometry that differed slightly about the ϕ and ψ torsion angles. Moreover, the X‐ray analysis of1 has been compared with that of the related unsaturated N‐amino‐imidazolin‐2‐one (Nai) analogs indicating the influences of ring flattening and substituents on conformation. Insertion of the preorganized Aid structure into biologically active peptides has thus been shown to offer a potentially valuable means for exploring the importance of turn geometry for activity, particularly in drug discovery. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 629–635, 2015.